Software Architectures for Humanoid Robotics - Fumio Kanehiro (Frontiers Research Topics, 2018)
In the past few years humanoid robots have evolved at a rapid pace. Research has made impressive advancements on both mechatronics and cognitive capabilities, including learning, perception and control. At the same time the explosion of the market of mobile devices has led to a remarkable increase in the computational capabilities of embedded CPUs and has made available higher resolution sensors and inertial units. Research on humanoid robotics is attacking problems such as human-robot interaction, whole body control, object manipulation and tool use. These research efforts must be supported by an adequate software infrastructure which allows experimenting with new hardware and algorithms while at the same time reducing debugging time and maximizing code-reuse. The complexity of humanoid robots and their peculiar application domain require that further software engineering efforts are devoted to support the proper integration of diverse capabilities. While research in mechatronics, motor control, learning and perception receive wide visibility in in international conference and journals, software tools and software engineering know-how are rarely shared among groups working on different platforms. This Research Topic invites submissions describing efforts in software engineering in the broad field of humanoid robotics.